Predictors of vitamin B12 deficiency among patients with skin hyperpigmentation attending the dermatology clinic at Acharya Vinoba Bhave rural hospital Wardha, India - Palma, Ogiza; Elioba, John L. R.; Raymond, David; Aimé, Aliunui; Madke, Bhushan (International Journal of Research in Dermatology, 2024)
Background: India like any other developing country is grappling with malnutrition cases due to avoidable factors. Nutritional deficiencies are prevalent in India and hyperpigmentation due to micronutrient deficiencies are common. Prevalence of B12 deficiency varies from 3% to 5% in the general population. This study aimed to determine the predictors of vitamin B12 deficiency among patients with skin hyperpigmentation AVBRH hospital, India. Methods: A cross-sectional study involving 164 patients with skin hyperpigmentation at dermatology department of AVBRH hospital, India was conducted from 1st April to June 30th 2024. Interviewer-administered questionnaires were used to obtained data and analysis was done using Stata version. Results: Of the 164 respondents, 73(44%) had vitamin B12 deficiency. The mean plasma vitamin B12 level was 201 pg/ml among strict vegans as compared to 314 pg/ml in non-strict vegans. Young age (OR=7.1; 95%CI: 1.120-2.737; p=0.009), distance more than 5 kilometers from nearest health facility (OR=3.8, 95%CI: 0.024-0.187; p=0.005), not employed (OR=2.5, 95%CI: 0.731-4.071; p=0.026), being strict vegetarian (OR=2.1, 95%CI: 0.141-1.050; p=0.002), and number of meals less than 3 per day (OR=9.1; 95%CI: 3.14-7.320, p=0.005) were independently associated with vitamin B12 deficiency among patients with skin hyperpigmentation at AVBRH hospital, India. Conclusions: The prevalence of Vitamin B12 deficiency among patients with skin hyperpigmentation is high in India. Young age, residing more than 5 kilometers from health facility, being a strict vegetarian, having less than 3 meals per day and unemployment are predictive for vitamin B12 deficiency among patients with skin hyperpigmentation at AVBRH hospital.